2001
DOI: 10.1177/104225870102500301
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of Entrepreneurial Learning

Abstract: We model entrepreneurial learning as a calibrated algorithm of an iterated choice problem in which entrepreneurs learn by updating a subjective stock of knowledge accumulated on the basis of past experiences. Specifically, we argue that entrepreneurs repeat only those choices that appear most promising and discard the ones that resulted in failure. The contribution of the paper is twofold. First, we provide a structural model of entrepreneurial learning in which failure is as informative—though clearly not as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
662
0
25

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 771 publications
(737 citation statements)
references
References 16 publications
14
662
0
25
Order By: Relevance
“…Recent studies of entrepreneurial cognition, such as Mitchell et al (2002) and Parker (2004) have been limited by the cognitivist paradigm of individual (not social) and cerebral (not behavioural) conceptualisation. The results can be seen in the algorithmic "dynamic model of entrepreneurial learning" produced by Minniti andBygrave (2001), As Spinosa et al (1997) observed, there is a need to move beyond such entitative and positivist approaches to entrepreneurship in order to create understanding of the human processes involved.…”
Section: Summary Of Relevant Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies of entrepreneurial cognition, such as Mitchell et al (2002) and Parker (2004) have been limited by the cognitivist paradigm of individual (not social) and cerebral (not behavioural) conceptualisation. The results can be seen in the algorithmic "dynamic model of entrepreneurial learning" produced by Minniti andBygrave (2001), As Spinosa et al (1997) observed, there is a need to move beyond such entitative and positivist approaches to entrepreneurship in order to create understanding of the human processes involved.…”
Section: Summary Of Relevant Literaturementioning
confidence: 96%
“…The model does not make claims or assertions about people's cognitive processes. There is, therefore, no basis for comparison with theories which propose rational or economic understanding of entrepreneurial behaviour rooted in cognitive theory (for example, Minniti and Bygrave: 2001;Mitchell et al, 2002;Shepherd and Krueger: 2002), Although cognitivism is pervasive and influential in the literature, as Gergen (1999) observes, there is a strong case to be made against simply accepting this and it is equally valid to propose a social constructionist alternative.…”
Section: Entrepreneurial Learningmentioning
confidence: 99%
“…Inward represents introspection about self (Minniti and Bygrave, 2001) while outward describes reflection about interaction with others. Backward considers reflection on past events (Daudelin, 1996) while forward represents visualisations about how the experience should change future actions (Gibb, 1997;Senge, 1990).…”
Section: Reflecting Inward Outward Backward and Forwardmentioning
confidence: 99%
“…Moving from the classroom to the laboratory, this methodology applies experiential learning where the student learns the business by doing it (Lackeus, 2015;Cope, 2005;Minniti and Bygrave, 2001), acquiring knowledge and developing entrepreneurial skills, abilities and competences (Borgese, 2011;Kiraly, 2011). From this point of view, it is exceeded the «talk and chalk approach» of the topics, encouraging a new way of learning business administration disciplines (Veneziani, 2012;Le Boterf, 2000).…”
Section: The Methodology Of Practice Firmmentioning
confidence: 99%